2015
DOI: 10.4172/2169-0316.1000177
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Thermal and Physical Properties of Magnesium Nitride Powder: Impact of Biofield Energy Treatment

Abstract: Magnesium nitride (Mg 3 N 2 ) has gained extensive attention due to its catalytic and optoelectronic properties. The present investigation was aimed to evaluate the effect of biofield energy treatment on physical and thermal properties of Mg 3 N 2 powder. The Mg 3 N 2 powder was divided into two parts i.e. control and treated. The control part was remained as untreated and the treated part was subjected to the Mr. Trivedi's biofield energy treatment. Subsequently, the control and treated Mg 3 N 2 samples were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
26
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 29 publications
0
26
0
Order By: Relevance
“…The percentage change in the isotopic abundance ratio of P M+1 /P M ( 2 H/ 1 H or 13 C/ 12 C or 17 O/ 16 O or 25 Mg/ 24 Mg) was significantly decreased in the treated sample by 48.87% compared to the control sample. Subsequently, the isotopic abundance ratio of P M+2 /P M ( 18 O/ 16 O or 26 Mg/ 24 Mg) in the treated sample was significantly increased by 29.18% compared with the control sample. In summary, 13 C, 2 H, 17 O, and 25 Mg contributions from (C 12 H 23 MgO 14 ) + to m/z 416; 18 O and 26 Mg contributions from (C 12 H 23 MgO 14 ) + to m/z 417 in the treated sample were significantly altered compared with the control sample.…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…The percentage change in the isotopic abundance ratio of P M+1 /P M ( 2 H/ 1 H or 13 C/ 12 C or 17 O/ 16 O or 25 Mg/ 24 Mg) was significantly decreased in the treated sample by 48.87% compared to the control sample. Subsequently, the isotopic abundance ratio of P M+2 /P M ( 18 O/ 16 O or 26 Mg/ 24 Mg) in the treated sample was significantly increased by 29.18% compared with the control sample. In summary, 13 C, 2 H, 17 O, and 25 Mg contributions from (C 12 H 23 MgO 14 ) + to m/z 416; 18 O and 26 Mg contributions from (C 12 H 23 MgO 14 ) + to m/z 417 in the treated sample were significantly altered compared with the control sample.…”
mentioning
confidence: 91%
“…This process is known as The Trivedi Effect ® -Energy of Consciousness Healing Treatment [17,18] [19]. Biofield Energy Treatment (The Trivedi Effect ® ) has been drawn attention more in the recent times for its scientifically measurable capability to transform the characteristic properties of a wide varieties living and nonliving substances such as plants [20,21], animals [22], microbes [23,24], cancer cells [25], medium [26,27], materials [28,29], pharmaceuticals [30,31], nutraceuticals [32,33], organic compounds [34,35]. The scientific study indicated that Biofield Energy Healing Treatment (The Trivedi Effect ® ) might be an alternate method for increasing or decreasing the natural isotopic abundance ratio of the substances [36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%
“…Biofield Energy Healing Treatment (The Trivedi Effect ® ) has been published in numerous peerreviewed science journals due to its significant impacts in the science fields of biotechnology, genetics, cancer, microbiology, materials science, agriculture, and pharmaceuticals. These publications reported that Biofield Energy Treatment (The Trivedi Effect ® ) has the astounding capability to transform the physical, structural, chemical, thermal and behavioral properties of several pharmaceuticals [23,24], nutraceuticals [25,26], organic compounds [27][28][29][30], metals and ceramics in materials science [31][32][33], improve the overall productivity of crops [34][35][36], as well as modulate the efficacy of various living cells [37][38][39][40]. Although magnesium gluconate displays the highest bioavailability and moderate solubility in water in comparison to other magnesium salts, humans still face problems in achieving their daily requirements of magnesium [41].…”
Section: Introductionmentioning
confidence: 99%
“…This process is known as The Trivedi Effect ® -Biofield Energy Healing Treatment [16,17] [18]. Biofield Energy Treatment (The Trivedi Effect ® ) has been extensively studied with significant outcomes in many scientific fields such as cancer research [19], altered antimicrobial sensitivity of pathogenic microbes in microbiology [20,21], genetics [22,23], biotechnology [24,25], altered physical and chemical properties of pharmaceuticals [26,27], nutraceuticals [28,29], organic compounds [30,31], improved overall growth and yield of plants in agricultural science [32,33], and changing the structure of the atom in relation to various metals, ceramics, polymers and chemicals in materials science [34,35]. The scientific study indicated that Biofield Energy Healing Treatment (The Trivedi Effect ® ) might be an alternate method for increasing or decreasing the natural isotopic abundance ratio of the substances [36][37][38].…”
Section: Introductionmentioning
confidence: 99%